The Turkish national minority in Bulgaria after 1945 - Stawowy-Kawka, Irena (Balcanica Posnaniensia. Acta et studia, 2010)
The article presents an in-depth analysis of the situation of the Turkish national minority in Bulgaria from the end of World War II to the beginning of the twenty-first century. The research begins with an examination of the Bulgarian authorities’ policies toward the Muslim population during the communist period, followed by the political transformation and Bulgaria’s accession to the European Union. The author seeks to trace the evolution of the Bulgarian state’s attitude toward the Turks-from the initial declarations of equality and integration, through successive stages of forced assimilation, to the democratic changes after 1989. The purpose of the study is to present the mechanisms shaping Bulgaria’s nationality policy toward the Turkish population and its social, political, and demographic consequences. The author draws on a wide range of sources: government documents, legal acts, statistical data, as well as Bulgarian and international studies, including reports by the European Commission and the EU Agency for Fundamental Rights. The analysis covers both the state’s migration and assimilation policies and the development of national identity and political activity within the Turkish minority. The author concludes that Bulgarian policy after 1945 was inconsistent, oscillating between attempts at integration and brutal forms of enforced Bulgarization, particularly during 1984–1989. Despite notable improvements following the collapse of Todor Zhivkov’s regime, Turks in Bulgaria still face certain linguistic and religious restrictions. Reports by European institutions confirm the ongoing integration of this community while also highlighting persistent social and economic challenges. The article reveals the complexity of Bulgarian–Turkish relations and underscores the importance of European standards in transforming national minority policies.